Q4 Syndrome in Public Sector Financial Management: Case and Evidence from a Spending Unit of Indonesia’s Ministry of Transportation - Emanuel Damarjati (Jurnal Akuntansi, 2026)
Purpose – This study aims to investigate the manifestation and underlying drivers of Q4 Syndrome, defined as the concentration of government expenditure in the final quarter of the fiscal year, within a working unit of Indonesia’s Ministry of Transportation. Design/Methodology/Approach – The research employs a quantitative case study approach using descriptive financial analysis. Monthly budget realization data, expenditure composition, and procurement/payment execution timing over a single fiscal year are analyzed to identify spending patterns and execution dynamics. Results –  The findings reveal a significant concentration of budget absorption in the fourth quarter, with a substantial proportion of annual expenditure executed during this period. Capital expenditures and procurement-related payments were heavily clustered in the final months, indicating delayed execution rather than evenly distributed disbursement throughout the fiscal year. Research limitations/Implications – The study provides case-based empirical evidence of Q4 Syndrome at the operational level. Institutional incentives—such as absorption-based performance evaluation, concerns over future budget reductions, and compliance-oriented controls—contribute to risk-averse spending behavior in earlier quarters. However, the single-unit case design limits generalizability. The findings highlight the need to shift performance measurement from absorption rates toward output-based indicators and to strengthen early-stage budget execution mechanisms. Keywords: Budget Absorption, Government Budget Execution, Public Sector Financial Management, Q4 Syndrome